Recombinant Service System Engineering - Beverungen, Daniel; Lüttenberg, Hedda; Wolf, Verena (Proceedings der 13. Internationalen Tagung Wirtschaftsinformatik (WI 2017))
Although many methods have been proposed for engineering services and customer solutions, most of these approaches give little consideration to recombinant service innovation. In an age of smart products and smart data, we can, however, expect that many of future service innovations need to be based on adding, transferring, dissociating, and associating existing value propositions. The purpose of this paper is to outline what properties constitute recombinant service innovation and to identify if current service engineering approaches fulfill these properties. Based on a conceptual in-depth analysis of 24 service engineering methods, we identify that most methods focus on designing value propositions instead of service systems, view service independent of physical goods, are linear or iterative, and incompletely address the mechanisms of recombinant innovation. We discuss how these deficiencies can be remedied and propose a first conceptual model of a revised se rvice system engineering approach.
Keywords: Service engineering; recombinant innovation; (product - )service system; literature analysis; new service development

Recommendation and Configuration of Value-Added Services for Repurposing Electric Vehicle Batteries: A Vertical Software Prototype - Klör, Benjamin; Monhof, Markus; Bräuer, Sebastian; Beverungen, Daniel (Proceedings of the 19th IEEE Conference on Business Informatics (CBI 2017))

Interaktive, digitale Einkaufserlebnisse in Innenstädten - Hendrik Betzing, Jan; Beverungen, Daniel; Becker, Jörg; Matzner, Martin; Schmitz, Gertrud; Bartelheimer, Christian; Berendes, Carsten Ingo; Braun, Marina; Gadeib, Andera; Hoffen}, Moritz {von; Schallenberg, Christian (HMD Praxis der Wirtschaftsinformatik)

Ensembles of Context and Form for Repurposing Electric Vehicle Batteries: An Exploratory Study - Beverungen, Daniel; Bräuer, Sebastian; Plenter, Florian; Klör, Benjamin; Monhof, Markus (Computer Science --- Research and Development)

Information systems for smart services - Beverungen, Daniel; Matzner, Martin; Janiesch, Christian (Information Systems and E-Business Management)
Digital interactions among businesses and consumers through powerful information systems and omnipresent connected devices establish today’s networked society. In this light, Service Science continues to take root as a research discipline that focuses on the integration of (digital) resources by service providers and service customers for value co-creation in service systems. Rapid advances in information technology allow for designing novel information systems that enable entirely new configurations of service systems. In turn, Service Science also leaves its mark on the design, adoption, and use of information systems and technology. With this special issue, we compile a set of timely papers that investigate selected facets of the complex interplay between information technology, information systems, and Service Science to design innovative IT artifacts for smart service. This editorial opens this special issue by elaborating on our understanding of smart service.<br
Keywords: Information system; Smart service; Service system

Design and Evaluation of a Model-Driven Decision Support System for Repurposing Electric Vehicle Batteries - Klör, B; Monhof, M; Beverungen, Daniel; Bräuer, S (European Journal of Information Systems (EJIS))

End-of-Life Solutions für eCar-Batterien --- Entwicklung hybrider Leistungsbündel und Informationssysteme zur Entscheidungsunterstützung (EOL-IS) - Becker, Jörg; Monhof, Markus; Beverungen, Daniel; Bräuer, Sebastian; Klör, Benjamin; Plenter, Florian (Dienstleistungen als Erfolgsfaktor für Elektromobilität. Ergebnisse aus dem Förderschwerpunkt “Dienstleistungsinnovationen für Elektromobilität”)

Informationsmodellierung in Dienstleistungssystemen - Beverungen, Daniel; Matzner, Martin (Handbuch Dienstleistungsmanagement)

Conceptualizing smart service systems - Beverungen, Daniel; Müller, Oliver; Matzner, Martin; Mendling, Jan; vom Brocke, Jan (Electronic Markets)

An open-data approach for quantifying the potential of taxi ridesharing - Barann, Benjamin; Beverungen, Daniel; Müller, Oliver (Decision Support Systems)
Taxi ridesharing1 (TRS) is an advanced form of urban transportation that matches separate ride requests with similar spatio-temporal characteristics to a jointly used taxi. As collaborative consumption, TRS saves customers money, enables taxi companies to economize use of their resources, and lowers greenhouse gas emissions. We develop a one-to-one TRS approach that matches rides with similar start and end points. We evaluate our approach by analyzing an open dataset of > 5 million taxi trajectories in New York City. Our empirical analysis reveals that the proposed approach matches up to 48.34% of all taxi rides, saving 2,892,036 km of travel distance, 231,362.89 l of gas, and 532,134.64 kg of CO2 emissions per week. Compared to many-to-many TRS approaches, our approach is competitive, simpler to implement and operate, and poses less rigid assumptions on data availability and customer acceptance.
Keywords: Taxi ridesharing Collaborative consumption Transportation Open data Sustainability Shared mobility

Residential Energy Storage from Repurposed Electric Vehicle Batteries — Market Overview and Development of a Service-Centered Business Model - Bräuer, sebastian; Monhof, Markus; Klör, Benjamin; Beverungen, Daniel (Proceedings of the IEEE Conference on Business Informatics (CBI 2016))

Will They Die Another Day? A Decision Support Perspective on Reusing Electric Vehicle Batteries - Beverungen, Daniel; Klör, Benjamin; Bräuer, Sebastian; Monhof, Markus (Proceedings of the Twenty-Third European Conference on Information Systems (ECIS 2015))

A Market for Trading Used Electric Vehicle Batteries — Theoretical Foundations and Information Systems - Klör, Benjamin; Beverungen, Daniel; Bräuer, Sebastian; Plenter, Florian; Monhof, Markus (Proceedings of the Twenty-Third European Conference on Information Systems (ECIS 2015))

A Domain-Specific Modeling Language for Electric Vehicle Batteries - Klör, Benjamin; Bräuer, Sebastian; Beverungen, Daniel; Monhof, Markus (Proceedings of the 12. International Conference on Wirtschaftsinformatik 2015 (WI 2015))

Extending Battery Management Systems for Making Informed Decisions on Battery Reuse - Monhof, Markus; Beverungen, Daniel; Klör, Benjamin; Bräuer, Sebastian (New Horizons in Design Science: Broadening the Research Agenda)

Dienstleistungsinnovationen für Elektromobilität: Märkte, Geschäftsmodelle, Kooperationen - Beverungen, Daniel; Fabry , Christian; Ganz , Walter; Matzner , Martin; Satzger , Gerhard

IT-basierte Dienstleistungen für die Elektromobilität --- Konzeptioneller Rahmen und Literaturanalyse - Klör, Benjamin; Bräuer, Sebastian; Beverungen, Daniel; Matzner, Martin (Proceedings of the Multikonferenz Wirtschaftsinformatik 2014 (MKWI 2014))

On the Ontological Expressiveness of Conceptual Modeling Grammars for Service Productivity Management - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Peter Rauer, Hans; Sigge, Daniel (Information Systems and e-Business Management)

Exploring the Interplay of the Design and Emergence of Business Processes as Organizational Routines - Beverungen, Daniel (Business and Information Systems Engineering)

Über das Zusammenwirken der Gestaltung und Emergenz von Geschäftsprozessen als Organisationsroutinen - Beverungen, Daniel (WIRTSCHAFTSINFORMATIK)

Effizienzmessung industrieller Dienstleistungen mittels Data Envelopment Analysis (ServDEA) - Backhaus, Klaus; Becker, Jörg; Beverungen, Daniel; Breuker, Dominic; Bröker, Ole; Alexander Brüne, Philipp; Dietrich, Hanns-Alexander; Knackstedt, Ralf; Peter Rauer, Hans; Reichle, Florian; Wilken, Robert (Produktivität von Dienstleistungen)

Performance Benchmarking for Designing Interaction Routines --- Managing Trade-offs in Service Co-creation with the Data Envelopment Analysis - Becker, Jörg; Beverungen, Daniel; Breuker, Dominic; Dietrich, Hanns-Alexander; Peter Rauer, Hans (Proceedings of the European Research Conference on Information Systems (ECIS) 2013)

On the Design of IT Artifacts and the Emergence of Business Processes as Organizational Routines - Beverungen, Daniel (Proceedings of the 34th International Conference on Information Systems (ICIS))

Local e-Government Transformation --- An International Comparison - Dillon, S; Deakins, E; Beverungen, Daniel; Kohlborn, T; Hofmann, S; Räckers, M (WEBIST)

Old Blunders in New Media? How Local Governments Communicate with Citizens in Online Social Networks - Hofmann, Sara; Räckers, Michael; Beverungen, Daniel; Becker, Jörg (Proceedings of the 46$^{th}$ Hawaii International Conference on System Sciences (HICSS-46))

Capitalizing on Social Media Analysis --- Insights from an Online Review on Business Models - Malsbender, Andrea; Beverungen, Daniel; Voigt, Matthias; Becker, Jörg (Proceedings of the Americas Conference on Information Systems (AMCIS2013))

Much Ado about Nothing? Tracing the Progress of Innovations Borne on Enterprise Social Network Sites - Malsbender, Andrea; Recker, Jan; Kohlborn, Thomas; Beverungen, Daniel; Tanwer, Satya (Proceedings of the 34th International Conference on Information Systems (ICIS))

Digital Social Signal Processing --- Theoretical Underpinning and Research Agenda - Malsbender, Andrea; Voigt, Matthias; Beverungen, Daniel; Rosemann, Michael (Proceedings of the Pacific Asia Conference on Information Systems (PACIS))

Unravelling (E-)Government Channel Selection: A Quantitative Analysis of Individual Customer Preferences in Germany and Australia - Plattfaut, Ralf; Kohlborn, Thomas; Hofmann, Sara; Beverungen, Daniel; Niehaves, Björn; Räckers, Michael; Becker, Jörg (Proceedings of the 46th Hawaii International Conference on System Sciences)

Guidelines for Reporting Productivity Studies: A Review of the Reproducibility of DEA in the Service Sector - Becker, Jörg; Beverungen, Daniel; Breuker, Dominic; Dietrich, Hanns-Alexander; Peter Rauer, Hans (International Journal of Services and Operations Management)

Bridging the Gap Between Manufacturing and Service Through IT-Based Boundary Objects - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Matzner, Martin; Müller, Oliver; Pöppelbuß, Jens (IEEE Transactions on Engineering Management)

Designing Interaction Routines in Service Networks: A Modularity and Social Construction-Based Approach - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Matzner, Martin; Müller, Oliver; Pöppelbuß, Jens (Scandinavian Journal of Information Systems)

Augmenting Analytical CRM Strategies with Social BI - Beverungen, Daniel; Eggert, Mathias; Voigt, Matthias; Rosemann, Michael (International Journal of Business Intelligence Research (IJBIR))

What Makes Local Governments' Online Communications Successful? Insights from a Multi-Method Analysis of Facebook - Hofmann, Sara; Beverungen, Daniel; Räckers, Michael; Becker, Jörg (Government Information Quarterly)

Verwaltungsdienstleistungen für Personen mit eingeschränkter Mobilität: Von mobilen Bürgerdiensten zu E-Government? - Plattfaut, Ralf; Hofmann, Sara; Kohlborn, Thomas; Beverungen, Daniel; Räckers, Michael; Niehaves, Björn; Becker, Jörg (eGovernment Review)

Softwaregestützte Konstruktion von Produktivitätsmodellen im Facility Management - Becker, Jörg; Bernhold, Torben; Beverungen, Daniel; Kaling, Nina; Knackstedt, Ralf; Vanessa, Lellek; Peter Rauer, Hans (Dienstleistungsmodellierung 2012: Product-Service Systems und Produktivität)

Softwaregestützte Konstruktion von Produktivitätsmodellen im Facility Management - Becker, Jörg; Bernhold, Torben; Beverungen, Daniel; Kaling, Nina; Knackstedt, Ralf; Vanesa, Lellek; Peter Rauer, Hans (Dienstleistungsmodellierung 2012)

Resolving trade-offs in Service Performance Benchmarking using Data Envelopment Analysis - Becker, Jörg; Beverungen, Daniel; Breuker, Dominic; Peter Rauer, Hans (Proceedings of the 16th Pacific Asian Conference on Information Systems (PACIS) 2012)

Service Productivity Management --- Status Quo and Directions for the Design of Conceptual Modeling Grammars. - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Peter Rauer, Hans; Sigge, Daniel (Proceedings of the 45th Hawaii International Conference on System Sciences (HICSS) 2012)

Global versus Local Properties of Service Science: Insights from a Comparative International Study on Research Results - Heide, Tobias; Tumbas, Sanja; Beverungen, Daniel; Knackstedt, Ralf; Becker, Jörg (Services and Economic Development: Local and Global Challenges)

Leveraging Social Network Data for Analytical CRM Strategies --- The Introduction of Social BI - Rosemann, Michael; Eggert, Mathias; Voigt, Matthias; Beverungen, Daniel (Proceedings of the 20$^{th}$ European Conference on Information Systems)

Construction of Productivity Models: A Tool Supported Approach in the Area of Facility Management - Becker, Jörg; Bernhold, Torben; Beverungen, Daniel; Kaling, Nina; Knackstedt, Ralf; Vanessa, Lellek; Peter Rauer, Hans (Enterprise Modelling and Information Systems Architectures)

Identifying e-Service Potential from Business Process Models --- A Theory Nexus Approach - Beverungen, Daniel; Knackstedt, Ralf; Winkelmann, Axel (e-Service Journal)

A Method for Selectively Designing Modeling Languages for Product-Service Systems - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf (Modeling for Decision Support in Network-Based Services: The Application of Quantitative Modeling to Service Science)

Ansätze zur methodischen Unterstützung der Konstruktion von Produktivitätsmodellen für die Data Envelopment Analysis --- Entwicklung eines Softwareprototypen zur Umsetzung und Evaluation - Becker, Jörg; Knackstedt, Ralf; Beverungen, Daniel; Dietrich, Hanns-Alexander; Breuker, Dominic; Peter Rauer, Hans (Service Engineering --- Management)

Product-Service System Approaches - Beverungen, Daniel; Matzner, Martin; Müller, Oliver; Becker, Jörg (Handbook of Service Description)

Conceptualizing Service Network Productivity --- A Looped DEA Approach - Becker, Jörg; Beverungen, Daniel; Breuker, Dominic (XII European Workshop on Efficiency and Productivity Analysis (Abstract))

How to Model Service Productivity for Data Envelopment Analysis? A Meta-Design Approach - Becker, Jörg; Beverungen, Daniel; Breuker, Dominic; Dietrich, Hanns-Alexander; Knackstedt, Ralf; Peter Rauer, Hans (ECIS 2011 Proceedings)

Do we need new theories on service productivity? --- Status Quo and implications from contemporary research - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Dietrich, Hanns-Alexander; Breuker, Dominic; Peter Rauer, Hans; Sigge, Daniel (XXI. International RESER Conference)

Information Needs in Service Systems --- A Framework for Integrating Service and Manufacturing Business Processes - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Matzner, Martin; Müller, Oliver (Proceedings of the 44th Annual Hawaii International Conference on System Sciences)